Tradisi sebagai Wadah Ketahanan Budaya: Sebuah Kritik terhadap Kapitalisme dan Budaya Pasar - SYUHENDRI - (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2008)
Tradition as Medium of Cultural Endurance: A Critic of Capitalism and Market Cultural. This studydiscusses the culture change in the postmodern era, and its effect on the world of art. Postmodern that emerged inparadigms and art creativity in Indonesia caused various effects, on the one hand can be seen as progress but on theother side become the cause of the decadence of cultural values.